2003
DOI: 10.1016/s0960-9822(03)00082-4
|View full text |Cite
|
Sign up to set email alerts
|

A SAGE Approach to Discovery of Genes Involved in Autophagic Cell Death

Abstract: Programmed cell death (PCD), important in normal animal physiology and disease, can be divided into at least two morphological subtypes, including type I, or apoptosis, and type II, or autophagic cell death. While many molecules involved in apoptosis have been discovered and studied intensively during the past decade, autophagic cell death is not well characterized molecularly. Here we report the first comprehensive identification of molecules associated with autophagic cell death during normal metazoan develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
185
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(187 citation statements)
references
References 21 publications
1
185
1
Order By: Relevance
“…79 An analysis of gene expression in Drosophila suggests that the TNFa-like pathway is involved during autophagic cell death in salivary glands. 80 Recently, the interaction of Atg5 with the death domain of FADD has been shown to play a crucial role in interferon-g-induced cell death independently of detectable activation of caspase-8. 81 Elucidation of signaling events downstream of FADD in Atg5-induced cell death would contribute to a better understanding of the control of autophagic cell death.…”
Section: Other Signaling Pathways Activated During Autophagic Cell Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…79 An analysis of gene expression in Drosophila suggests that the TNFa-like pathway is involved during autophagic cell death in salivary glands. 80 Recently, the interaction of Atg5 with the death domain of FADD has been shown to play a crucial role in interferon-g-induced cell death independently of detectable activation of caspase-8. 81 Elucidation of signaling events downstream of FADD in Atg5-induced cell death would contribute to a better understanding of the control of autophagic cell death.…”
Section: Other Signaling Pathways Activated During Autophagic Cell Deathmentioning
confidence: 99%
“…Genome-wide scale investigations have shown that, during autophagic cell death in Drosophila, the expression of a large array of genes, including several ATG genes (ATG2, 4-7, and 12), is upregulated. 80,83 Accumulation of ATGs has also been observed in mammalian cells undergoing autophagic cell death, and is dependent on the expression of proteins of the Bcl-2 family (Bcl-2 and Bc1-xL). 68 An accumulation of Beclin 1 has been reported during tamoxifen-induced autophagy.…”
Section: Jun N-terminal Kinase (Jnk)mentioning
confidence: 99%
“…56 The overlap between the molecular mechanisms mediating autophagic cell death and apoptosis is also reflected in the results of microarray studies and serial analysis of gene expression during developmental programmed cell death of the Drosophila salivary glands, where genes involved in both apoptosis and autophagy share similar expression profiles. 32,34 Several apoptotic stimuli can promote compensatory autophagic cell death, in particular when the apoptotic pathway is impaired. Suppression of caspase-8 activity induces non-apoptotic cell death in mouse L929 cells.…”
Section: Autophagy-apoptosis Interplaymentioning
confidence: 99%
“…Nine of these 11 apgrelated genes are transcribed in dying Drosophila glands, and the seven genes that are most similar to apg2 (CG1241), apg3 (CG6877), apg4 (CG6194), apg5 (CG1643), apg7 (CG5489), apg9 (CG3615), and aut10/cvt18 (CG7986) exhibit increased transcription following the rise in steroid hormone that triggers autophagic programmed cell death of this tissue. 36,64 It is interesting that flies possess genes that are related to the yeast genes involved in both of the autophagy ubiquitin conjugation systems, and that they are also the genes that increase in transcription following the rise in steroid that triggers autophagic cell death. CG1241 encodes a novel protein that is similar to APG2 that functions in the formation and completion of autophagic vacuoles.…”
Section: Cytoplasmmentioning
confidence: 99%
“…Steroids usually function by activating transcription and, therefore, it is not surprising that transcription regulators are induced in dying salivary glands including the corepressors (Smarter and CG4756), the NFkB regulator cactus, the NFkB family member dif, several other genes encoding DNA-binding proteins (bun, sox14, CG8319), and components of transcription complexes (trap95 and hsf). 36,64 Salivary gland cells exhibit dynamic changes in cell shape and vacuole localization just before autophagic cell destruction, suggesting that cytoplasmic reorganization and proteolysis are important for their death. Consistent with this notion, genes encoding motor proteins including ctp, ck, and dlc90F, and members of the Rho, Rac, and Rab families of small guanosine triphosphates (GTPases) exhibited increase in transcription just before salivary gland autophagic cell death.…”
Section: Br-c E74a E93mentioning
confidence: 99%